Abdulahad Nuri Sivasi’nin “Hikmetu’t-Tenaruz Fi Surati’t Tenakuz” adlı eseri - Bal, Mehmet Turan (My University, 2013)
TEZ ÖZETİ XVII. yy alimlerinden Abdulahad Nuri Sivasi’nin “Hikmetu’t-Teâruz fî Sûrati’t-Tenâkuz” adlı eseri tezimizde tenkitli olarak neşredilmiş, müellif, yaşadığı zaman ve eseri hakkında bilgi verilmiştir. Sivasiler diye bilinen meşhur bir ailenin önde gelen bir ferdi olan Abdulahad Nuri (1594/ 1651) kırk küsür haifesiyle önde gelen bir halveti şeyhidir. Halvetilikteki Sivasiyye bölümünün kurucusudur. Osmanlıda protokolde yerini bulan bir kürsü şeyhidir. Doğumu Sivas vefatı İstanbul Eyup’tür. Müellif meşhur Kadızade-sivasi polemiğinin en önemli taraflarından birisidir. Meşhur Şemseddin Sivasi’nin akrabasıdır. Bu eser müşkili’l- Kur’an ilmiyle ilgili çok önemli, tek nüshası Köprülü Kütüphanesinde bulunan talik bir yazmanın çözümüdür.

Publicatıon of “Hikmetu’t-Teâruz fî Sûrati’t-Tenâkuz” Titled Manuscript by Abdulahad Nûrî Sivâsî Abdulahad Nûrî Sivâsî was born in 1594 in the city of Sivas. His family moved from Sivas to İstanbul. He grew up in the capital of the Ottoman Empire. At that days Ottomans was at their peak. Then something had started to go wrong for the empire. His family was very famous as “Sivâsîler” (plural of Sivâsî). Especially in the famous argument of the XVIIth. century: “Kadızâdes (plural of Kadızâde) and Sivâsîs”. Also he was a master of the Şemsiyye branched from Halvetiyye order. There were two famous master in the famous master in the family: His granduncle; Şemseddin Sivâsî and his uncle; Abdülmecid Sivâsî. Nûrî Sivâsî is the organisator of the Sivâsiyye branch. He trained about fifty khalifas and sent them to the several regions of the empire. He was very important person in the science history as a master, as a poet having “divan” and about fourty anthem which were set to music and as a scientist who had serious of twenty works before his twenties. He died in 1651 in İstanbul. His tomb is at Nişanca Eyüp. This manuscript so important cause of there is no another reproduction. It was written about understanding confix in the Qur’anic research. Qur’an Serves understanding levels. But some of the extreme idea owners may have used this situation, against to the main sistem of the religion. Author doesn’t let them systematize their excessive and heretic ideas in the willing and winning of the love and price of the great creator. So did I. We are glad to introduce this special manuscript to the world of science.
Keywords: Biyografi; İslam; Kur'an-ı Kerim; Mutasavvıflar; Sivasi, Abdulahad Nuri; Tefsir Bilimi